Manajemen anestesi pada operasi koreksi deformitas skoliosis - Moses Wijaya; I Wayan Widana (Intisari Sains Medis, 2022)
Background: Adolescent Idiopathic Scoliosis (AIS) is a lateral curvature of the spine with a bulge angle of at least 10°, with no underlying neuromuscular or congenital abnormality. Surgery is the best treatment for patients with AIS. The main goal of AIS surgery is to prevent progression due to fusion, but there are various potential risks, such as the postoperative period. Case: The patient was a 26-year-old female patient with complaints of an misaligned spine. The patient was diagnosed with adolescent idiopathic scoliosis and planned for scoliosis deformity correction. The X-ray shows a thoracic curve with convexity to the right (7th thoracic vertebrae – 1st lumbar vertebra), Cobb angle 54 degrees, right Cobb bending angle 34 degrees, flexibility 20 degrees, left Cobb bending angle 70 degrees, flexibility 26 degrees. The operation was performed using the general anesthesia-orotracheal tube (GA-OTT) technique. After induction, the patient was placed in the prone position. Maintenance of anesthesia with O2, N2O, dexmetomidine, intermittent fentanyl, and rocuronium. The operation lasted for 6 hours, the bleeding during the operation was 1000 ml and was hemodynamically stable. Post-operatively the patient is well conscious and adequate spontaneous breathing. Patient care is carried out in the ICU with the administration of analgesics. Conclusion: Adolescent idiopathic scoliosis is an exception diagnosis from other forms of scoliosis. An approach to find out the causes, risk factors, methods of diagnosis and treatment of patients with adolescent idiopathic scoliosis are needed in order to increase the success of therapy and the quality of life of the patients.   Latar Belakang: Adolescent Idiopathic Scoliosis (AIS) adalah kelengkungan lateral tulang belakang dengan sudut tonjolan minimal 10°, tanpa kelainan neuromuskular atau bawaan yang mendasarinya. Pembedahan adalah pengobatan terbaik untuk pasien dengan AIS. Tujuan utama operasi AIS adalah untuk mencegah perkembangan akibat fusi, tetapi ada berbagai potensi risiko, seperti periode pasca operasi. Laporan Kasus: Pasien wanita berusia 26 tahun dengan keluhan bentuk tulang belakang yang tidak lurus. Pasien didiagnosis dengan adolescent idiopathic scoliosis dan direncanakan untuk scoliosis deformity correction. Pada rongent tampak curve thoracalis dengan konveksitas ke kanan (vertebra thorakalis 7 – vertebra lumbal 1), sudut Cobb 54 derajat, sudut Cobb Bending kanan 34 derajat, flexibilitas 20 derajat, sudut Cobb Bending kiri 70 derajat, flexibilitas 26 derajat. Operasi dilakukan dengan teknik anestesi general anesthesia-orotracheal tube (GA-OTT). Setelah dilakukan induksi, pasien diatur ke posisi prone. Pemeliharaan anestesi dengan O2, N2O, dexmetomidine, fentanyl intermitten, dan rocuronium. operasi berlangsung selama 6 jam, perdarahan selama operasi 1000 ml dan hemodinamik stabil. Post-operative pasien sadar baik dan bernafas spontan adekuat. Perawatan pasien dilakukan di ICU dengan pemberian analgetik. Simpulan: Adolescent idiopathic scoliosis adalah diagnosis pengecualian dari bentuk skoliosis lainnya. Penelusuran untuk mengetahui penyebab, faktor risiko, metode diagnosis dan tatalaksana dari pasien dengan adolescent idiopathic scoliosis diperlukan agar dapat meningkatkan keberhasilan terapi dan kualitas hidup dari pasien.